Biological DMARDs and disease modification in axial spondyloarthritis - Sepriano, Alexandre (2021)
Funding Information: Competing interests AS: Consulting/speaking fees from MSD, UCB, Novartis. SR: Research grant from MSD; Consultancy/speaking fees from AbbVie, Eli Lilly, MSD, Novartis, UCB, Sanofi. DvdH: Consulting fees AbbVie, Amgen, Astellas, AstraZeneca, Bayer, BMS, Boehringer Ingelheim, Celgene, Cyxone, Daiichi, Eisai, Eli-Lilly, Galapagos, Gilead, Glaxo-Smith-Kline, Janssen, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi, Takeda, UCB Pharma Director of Imaging Rheumatology bv. RL: Consulting fees from AbbVie, BMS, Celgene, Eli-Lilly, Galapagos, Gilead, Glaxo-Smith-Kline, Janssen, Merck, Novartis, Pfizer, Roche, UCB and is Director of Rheumatology Consultancy bv Publisher Copyright: ©